USE OF GLYCEROL AS CRYOPROTECTANTS IN FREEZING SENTUL CHICKEN SEMEN - J. Junaedi; Raden Iis Arifiantini; Cece Sumantri; Asep Gunawan (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
On the freezing semen chicken cryoprotectants required to overcome the damage of spermatozoa due to cold shock. This study aims to get the best concentrations of cryoprotectants glycerol concentration of 5%, 7% and 9% in freezing Sentul chicken semen. The semen used in this study came from three chickens Sentul and be repeated nine times. Semen was collected by messase methods for three times a week. Semen was evaluated macroscopic and microscopic. Furthermore spermatozoa diluted with egg yolk and the addition of three concentrations of cryoprotectants glycerol (5%, 7% and 9%). Semen diluted 0:25 ml is packed into straw. Then equilibrated at a temperature of 5°C for two hours. After equilibration to evaluate the motility and viability of spermatozoa. Furthermore, frozen in liquid nitrogen vapor for 10 minutes. Frozen semen is then stored in liquid nitrogen containers with temperature -196°C. After 24 hours, semen is thawed at 37°C for 30 seconds. The results showed that the percentage of sperm motility and viability of frozen semen cock Sentul using glycerol cryoprotectants 5% better P (0.05) compared with the use of glycerol 7% and 9%. The use of glycerol 5% at this stage of equilibration and storage can reduce the damage of spermatozoa in the semen of chicken Sentul. Neither glycerol 5% could increase recovery rate after thawing